Manufacturing method of chip-type high-molecular tantalum electrolytic capacitor
By finely controlling the voltage, temperature and conductivity during the empowerment process and using a segmented boost method, the problem of uneven oxide film is solved, and the performance of the chip polymer tantalum electrolytic capacitor is significantly improved, including higher capacitance value and lower ESR value.
Patent Information
- Application Number
- CN202411985271.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-22
AI Technical Summary
The existing chip polymer tantalum electrolytic capacitors have problems such as unevenness and insufficient density during the formation and empowerment of oxide films, resulting in fluctuations in capacitor performance, high leakage current, unstable ESR value, and narrowing of operating temperature range.
By finely controlling the voltage, temperature and conductivity during the empowerment process, and using a segmented boost method, we ensure that a uniform and dense oxide film is formed on the surface of the anode tantalum block. The specific steps include adjusting the conductivity of the empowered liquid to 1500-1700μS/cm, adopting a segmented boosting method, and heat treatment of the energized anode tantalum block.
The performance of chip polymer tantalum electrolytic capacitors is significantly improved, including higher capacitance value, lower ESR value, stable long-term use performance and higher reliability.
Smart Images

Figure BDA0005222443480000061 
Figure BDA0005222443480000071 
Figure BDA0005222443480000091
Abstract
Description
Technical Field
[0001] The invention relates to a method for manufacturing a chip-type polymer tantalum electrolytic capacitor. Background Art
[0002] Tantalum electrolytic capacitors are capacitors with excellent electrical properties, and are widely used in high frequency, low ESR (equivalent series resistance), long life, and stability. Especially in chip-type polymer tantalum electrolytic capacitors, since conductive polymers are used as electrolytes, they can effectively reduce ESR, provide higher stability and longer service life, and thus become an indispensable component in electronic equipment.
[0003] One of the core performances of chip polymer tantalum electrolytic capacitors comes from the surface oxide film of its anode tantalum block. The oxide film not only acts as a dielectric layer, but also determines the key performance of the capacitor, such as rated voltage, current, and temperature resistance. The thickness and uniformity of the oxide film are crucial to the performance of the capacitor. In order to obtain a good oxide film, an anodizing (energizing) process is usually adopted, in which the control of the energizing voltage, the adjustment of the conductivity of the energizing liquid, and the control of the temperature all need to be strictly controlled. However, the prior art still has several problems and technical defects in the formation and energizing process of the oxide film, which affects the electrical performance stability and production efficiency of the capacitor.
[0004] In the traditional manufacturing process of tantalum electrolytic capacitors, the anode tantalum block often has problems such as uneven oxide film thickness and insufficient film density during the empowerment process. This is mainly due to the fact that the empowerment voltage boost rate is too fast or improper, resulting in inconsistent electrochemical reaction rates on the surface of the tantalum block, resulting in an uneven film layer and poor film density. Uneven film layers can cause performance fluctuations in the capacitor, which are specifically manifested in excessive leakage current, unstable ESR value, and a narrow operating temperature range. Such problems not only affect the quality of the capacitor, but also make it easy for a high scrap rate to occur during the production process, increasing production costs.
[0005] In the existing empowering process, a too fast boost rate or inaccurate temperature control often causes local overheating of the tantalum block surface or cracks or defects on the oxide film surface. A too fast boost may cause a sudden temperature rise, resulting in thermal stress concentration, leading to uneven or damaged film layers. Improper temperature control may result in the film layer not being fully formed, affecting the dielectric strength of the film and the long-term stability of the capacitor. Especially during the high-voltage empowering process, the gradual change in temperature should be kept accurate to avoid a decrease in the quality of the film layer due to sudden temperature changes.
[0006] The conductivity of the energy-enabling liquid has an important influence on the quality of the oxide film. If the conductivity of the energy-enabling liquid is too high or too low, it will affect the rate of the electrochemical reaction, thereby affecting the quality of the oxide film. In the prior art, the conductivity of the energy-enabling liquid is often not accurately controlled, resulting in unstable quality of the oxide film during the energy-enabling process. Unstable conductivity may lead to differences in thickness and density of the electrolyte membrane in different areas, thereby affecting the performance of the capacitor.
[0007] After being energized, the tantalum anode block needs to undergo a heat treatment process to enhance the stability of the oxide film and eliminate possible stress. However, in traditional processes, the control of the heat treatment process is often not precise enough, which can easily lead to the failure to completely release the thermal stress of the film layer, thus affecting the long-term stability and reliability of the capacitor. Insufficient heat treatment may cause the performance of the capacitor to deteriorate under high temperature conditions, thereby shortening the service life of the capacitor.
[0008] Due to the uneven quality of the oxide film and the inaccurate control of temperature and conductivity, the key performance of chip polymer tantalum electrolytic capacitors - especially ESR value, leakage current, operating voltage and capacity - is prone to fluctuations. This not only affects the normal use of the capacitor, but may also cause circuit failures, damage electronic components, and reduce the reliability of the equipment. With the growing demand for high performance of electronic equipment, how to stabilize and improve the performance of capacitors has become an important technical issue that needs to be urgently solved in the current capacitor manufacturing process. Summary of the invention
[0009] In view of the deficiencies in the prior art, the present invention provides a method for manufacturing a chip-type polymer tantalum electrolytic capacitor, which solves the problem of uneven and unstable oxide film by finely controlling the voltage, temperature and conductivity during the energizing process and adopting a segmented boosting method, thereby significantly improving the performance of the chip-type polymer tantalum electrolytic capacitor, including higher capacitance value, lower ESR value, stable long-term performance and higher reliability.
[0010] The technical solution adopted by the present invention to solve its technical problem is:
[0011] A method for manufacturing a chip-type polymer tantalum electrolytic capacitor comprises the following steps:
[0012] Tantalum powder with a specific capacity of 23000uF·V / g is used to press into a tantalum embryo, and then sintered to obtain a tantalum anode block;
[0013] Adjust the conductivity of the energizing solution to 1500-1700us / cm to form a uniform and dense oxide film on the surface of the anode tantalum block;
[0014] The following step-by-step boost method is used for empowerment:
[0015] Initial stage: the voltage gradually increases from 0V to 80V, the constant voltage time is 120 minutes, and the temperature is maintained at 90℃;
[0016] Intermediate stage: After 120 minutes of constant voltage at 80V, the voltage is increased to 100V and kept constant for 120 minutes, and the temperature is maintained at 90℃.
[0017] Final stage: the voltage is increased from 100V to the target enabling voltage, the constant voltage time is 180 minutes, and the temperature is gradually reduced to 80℃;
[0018] The energized tantalum anode block is heat treated.
[0019] Preferably, the pretreatment process of the anode tantalum block includes: preparing a pretreatment solution, mixing a silane coupling agent, glacial acetic acid and water in a volume ratio of 1:1:10, soaking the anode tantalum block for 30 minutes, taking out the anode tantalum block, and then drying it.
[0020] Preferably, after heat treatment, a conductive polymer is coated on the surface of the anode tantalum block so that the conductive polymer layer is evenly distributed on the surface of the anode tantalum block. The coated anode tantalum block is first dried at 80°C for 20 minutes and then dried at 150°C for 45 minutes.
[0021] Preferably, the energizing liquid is an electrolyte, which is an aqueous solution containing phosphate ions and oxygen ions.
[0022] Preferably, the heat treatment temperature is 450° C. and the treatment time is 60 minutes.
[0023] The beneficial effects of the present invention are:
[0024] By adjusting the conductivity of the energy-enhancing liquid to 1500-1700μS / cm and adopting a segmented pressure-increasing method, a uniform and dense oxide film can be formed on the surface of the anode tantalum block. The regulation of the conductivity of the energy-enhancing liquid helps to control the rate of the electrochemical reaction, thereby optimizing the quality and uniformity of the film; the segmented pressure-increasing method (including the initial stage, the intermediate stage and the final stage), combined with temperature control at different stages (gradually decreasing from 90°C to 80°C), can avoid thermal stress and local overheating caused by excessive pressure increase, and ensure the uniformity of the film layer on the surface of the anode tantalum block and the stability of the film during the energy-enhancing process.
[0025] The slow voltage increase in the initial stage helps to avoid damage to the oxide film due to excessive voltage; the constant voltage and appropriate temperature in the intermediate stage further promote the uniformity of the film; the slow voltage increase and constant voltage process in the final stage ensures that the target enabling voltage is reached and promotes the stability of the film by cooling. The stability of the oxide film and the overall performance of the tantalum capacitor can be further enhanced by heat treatment of the tantalum anode block after empowerment. The heat treatment process helps to eliminate the stress that may occur during the empowerment process, increase the mechanical strength of the film, and improve the long-term stability, durability and reliability of the capacitor. Specific implementation methods
[0027] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. The present invention is described more specifically by way of example in the following paragraphs. According to the following description and claims, the advantages and features of the present invention will become clearer.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0029] Embodiment 1:
[0030] A method for manufacturing a chip-type polymer tantalum electrolytic capacitor comprises the following steps:
[0031] Tantalum powder selection: Tantalum powder with a specific capacitance of 23000 μF·V / g is used, pressed into a tantalum embryo according to conventional technology, and sintered to obtain anode tantalum blocks.
[0032] Electrical conductivity of the energizing solution: The electrical conductivity of the energizing solution is adjusted to 1600μS / cm to ensure that a uniform and dense oxide film is formed on the surface of the anode tantalum block.
[0033] Enabling staged boost process:
[0034] Initial stage: the voltage gradually increases from 0V to 80V, the constant voltage time is 120 minutes, and the temperature is maintained at 90℃;
[0035] Intermediate stage: After 120 minutes of constant voltage at 80V, the voltage is increased to 100V and kept constant for 120 minutes, and the temperature is maintained at 90℃.
[0036] Final stage: The voltage is increased from 100 V to the target enabling voltage (120 V), the constant voltage time is 180 minutes, and the temperature is gradually reduced to 80°C.
[0037] Pretreatment process: prepare pretreatment solution, mix silane coupling agent, glacial acetic acid and water in a volume ratio of 1:1:10, soak the anode tantalum block for 30 minutes, take out the anode tantalum block and dry it.
[0038] Heat treatment: The heat treatment temperature was set to 450°C and the treatment time was 60 minutes.
[0039] Conductive polymer coating: Coat the surface of the heat-treated tantalum anode block with a conductive high polymer. After the coating is evenly distributed, first dry it at 80°C for 20 minutes and then dry it at 150°C for 45 minutes.
[0040] Embodiment 2:
[0041] A method for manufacturing a chip-type polymer tantalum electrolytic capacitor comprises the following steps:
[0042] Tantalum powder selection: Tantalum powder with a specific capacitance of 23000 μF·V / g is used, pressed into a tantalum embryo according to conventional technology, and sintered to obtain anode tantalum blocks.
[0043] Electrical conductivity of the energizing solution: The electrical conductivity of the energizing solution was adjusted to 1700 μS / cm to improve the formation efficiency of the oxide film.
[0044] Enabling staged boost process:
[0045] Initial stage: the voltage gradually increases from 0V to 80V, the constant voltage time is 120 minutes, and the temperature is maintained at 90℃;
[0046] Intermediate stage: After 120 minutes of constant voltage at 80V, the voltage is increased to 100V and kept constant for 120 minutes, and the temperature is maintained at 90℃.
[0047] Final stage: The voltage is increased from 100 V to the target enabling voltage (120 V), the constant voltage time is 180 minutes, and the temperature is gradually reduced to 80°C.
[0048] Pretreatment process: prepare pretreatment solution, mix silane coupling agent, glacial acetic acid and water in a volume ratio of 1:1:8, soak the anode tantalum block for 25 minutes, take out the anode tantalum block and dry it.
[0049] Heat treatment: The heat treatment temperature was set to 460°C and the treatment time was 70 minutes.
[0050] Conductive polymer coating: Coat the surface of the heat-treated tantalum anode block with a conductive high polymer. After the coating is evenly distributed, first dry it at 90°C for 15 minutes and then dry it at 155°C for 50 minutes.
[0051] Embodiment 3:
[0052] A method for manufacturing a chip-type polymer tantalum electrolytic capacitor comprises the following steps:
[0053] Tantalum powder selection: Tantalum powder with a specific capacitance of 23000 μF·V / g is used, pressed into a tantalum embryo according to conventional technology, and sintered to obtain anode tantalum blocks.
[0054] Electrical conductivity of the energizing liquid: The electrical conductivity of the energizing liquid is adjusted to 1500μS / cm to ensure that a uniform and dense oxide film is formed on the surface.
[0055] Enabling staged boost process:
[0056] Initial stage: the voltage gradually increases from 0V to 80V, the constant voltage time is 120 minutes, and the temperature is maintained at 90℃;
[0057] Intermediate stage: After 120 minutes of constant voltage at 80V, the voltage is increased to 100V and kept constant for 120 minutes, and the temperature is maintained at 90℃.
[0058] Final stage: The voltage is increased from 100 V to the target enabling voltage (120 V), the constant voltage time is 180 minutes, and the temperature is gradually reduced to 80°C.
[0059] Pretreatment process: prepare pretreatment solution, mix silane coupling agent, glacial acetic acid and water in a volume ratio of 1:1:12, soak the anode tantalum block for 35 minutes, take out the anode tantalum block and dry it.
[0060] Heat treatment: The heat treatment temperature was set to 450°C and the treatment time was 60 minutes.
[0061] Conductive polymer coating: Coat the surface of the heat-treated tantalum anode block with a conductive high polymer. After the coating is evenly distributed, first dry it at 75°C for 25 minutes and then dry it at 140°C for 60 minutes.
[0062] In the manufacturing process of tantalum capacitors, tantalum powder is used to make anode tantalum blocks, and the surface of the anode tantalum blocks is oxidized to form a tantalum oxide film (i.e., the electrolyte oxide film of tantalum). The quality of the oxide film directly affects the performance of the capacitor, especially its voltage tolerance and capacitance value. The uniformity, density and film thickness of the oxide film are very critical, so precise process control is required to ensure its high quality.
[0063] Conductivity of Energizing Fluid
[0064] The enabling solution (also called electrolyte) plays a vital role in the manufacture of tantalum capacitors. It determines the efficiency of oxide film formation. The higher the conductivity of the enabling solution, the faster and more uniform the oxide film formation will usually be. However, too high conductivity may lead to unstable film thickness and structure, so it is usually adjusted according to process requirements.
[0065] A higher conductivity (such as 1700 μS / cm in Example 2) can accelerate the formation process of the oxide film and reduce the time, but it may have a certain impact on the density and uniformity of the film.
[0066] A lower conductivity (such as 1500 μS / cm in Example 3) may result in a longer formation time, which helps to improve the quality of the membrane, but requires more time and energy.
[0067] Step-by-step boost process
[0068] The voltage increase process is usually carried out in stages, the purpose of which is to finely control the growth of the oxide film and prevent the film from growing too fast or too slow. The voltage increase process can be divided into the following stages:
[0069] Initial stage: Starting from a low voltage and gradually increasing the voltage, the main purpose is to avoid the damage of the oxide film by instantaneous high voltage.
[0070] Intermediate stage: Stabilize the oxide film at a lower voltage to increase the stability of the film.
[0071] Final stage: further boosting the voltage to the target voltage to ensure the final thickness and uniformity of the oxide film.
[0072] Different boosting process time and voltage settings will have different effects on the quality of the membrane.
[0073] Pretreatment and heat treatment
[0074] The pretreatment step is to optimize the surface state of the tantalum block by chemical means, making it easier to react with the energizing liquid to form a better oxide film. The heat treatment process is used to eliminate the internal stress that may be generated in the tantalum block during the sintering process and improve its overall performance.
[0075] Conductive polymer coating
[0076] The purpose of conductive polymer coating is to enhance the conductivity and stability of the oxide film, and also to help improve the performance of the capacitor, such as reducing the equivalent series resistance (ESR). The control of temperature and time during the coating process has a great influence on the coating quality.
[0077] The comparison of the above embodiments 1-3 is as follows:
[0078]
[0079]
[0080] Example 2 uses a higher conductivity (1700 μS / cm), which helps to improve the efficiency of oxide film formation, but may affect the uniformity and density of the film; Example 3 uses a lower conductivity (1500 μS / cm), which helps to improve the quality of the oxide film, but may require a longer processing time; The conductivity of Example 1 is set to 1600 μS / cm, which is a moderate choice aimed at balancing the efficiency and quality of oxide film formation.
[0081] The boost time and voltage of Example 2 are relatively high, especially in the final stage, the target voltage is raised to 130V, and a longer constant voltage time (240 minutes) is required compared to other examples. This indicates that this process may be suitable for capacitors that require higher voltage tolerance; the boost process of Example 3 is relatively long, but the target voltage is set to 110V, which is lower than other examples, and may pay more attention to the quality and stability of the membrane.
[0082] The second embodiment uses less water, which may accelerate the reaction between the silane coupling agent and the surface of the tantalum block, and contribute to a faster pretreatment reaction; the third embodiment uses more water, which may slow down the reaction rate and make the pretreatment process milder.
[0083] The heat treatment temperature of Example 2 is slightly higher (460°C) and the time is slightly longer (70 minutes), which may help to more thoroughly remove the internal stress of the tantalum block and improve the quality of the film; the heat treatment conditions of Example 1 and Example 3 are relatively close, both at 450°C and 60 minutes, indicating that the heat treatment of these examples is relatively standard.
[0084] The coating conditions of Example 2 and Example 3 are slightly different in time and temperature, which may affect the quality and performance of the coating. For example, Example 2 has a shorter coating time but a higher temperature, while Example 3 is dried at a lower temperature for a longer time.
[0085] There are differences between the first, second and third embodiments in terms of conductivity of the energizing liquid, boosting process, ratio of the pretreatment liquid, heat treatment and conductive polymer coating. These differences affect the quality of the oxide film, the performance of the capacitor and the efficiency of the production process. In general, the second embodiment is suitable for occasions requiring higher voltage tolerance and faster oxide film formation, while the third embodiment focuses on the compactness and uniformity of the oxide film. The first embodiment is a standard process suitable for production with general needs.
[0086] Experimental example
[0087] Purpose
[0088] By comparing the electrical performance parameters of chip polymer tantalum electrolytic capacitors produced by the traditional process and the new process (based on Examples 1-3), the effect of the new process on improving the performance of the capacitors was evaluated, especially in terms of capacitance (C), equivalent series resistance (ESR), leakage current (I0) and loss tangent (D).
[0089] Experimental Materials and Methods
[0090] Tantalum powder selection: Tantalum powder with a specific capacitance of 23000 μF·V / g is used, pressed into a tantalum embryo according to conventional technology, and sintered to obtain anode tantalum blocks.
[0091] Electrical conductivity of the energy-enhancing liquid: The electrical conductivity of the energy-enhancing liquid is adjusted according to different processes:
[0092] Original process: conductivity was not specially adjusted;
[0093] New process (Examples 1-3): The conductivity of the energizing liquid was adjusted to 1600 μS / cm (Example 1), 1700 μS / cm (Example 2) and 1500 μS / cm (Example 3), respectively.
[0094] Enabling step-by-step boosting process: The oxide film is formed according to the step-by-step boosting process in Examples 1-3, and constant pressure and temperature control are performed according to the parameters of each example.
[0095] Pretreatment process: According to different embodiments, different volume ratios of silane coupling agent and glacial acetic acid water are used for pretreatment, and the tantalum block is soaked for a certain period of time and then cleaned and dried.
[0096] Heat treatment process: The heat treatment temperatures in Examples 1-3 are set to 450° C. and 460° C., respectively, and the treatment time is 60-70 minutes to ensure that the internal stress of the tantalum block is eliminated.
[0097] Conductive polymer coating: Conductive polymer coating was performed according to the specified temperature and time of each example to ensure uniformity and stability of the coating.
[0098] Experimental Procedure
[0099] Original process preparation:
[0100] Chip polymer tantalum electrolytic capacitors are prepared using traditional processes and are processed according to standard energy-enabling solution formulations, voltage boosting processes, and heat treatment procedures.
[0101] The electrolyte preparation and pretreatment adopt conventional processes to ensure that all experimental conditions meet the original process standards.
[0102] New process preparation:
[0103] A chip-type polymer tantalum electrolytic capacitor was prepared according to the process conditions of Examples 1-3.
[0104] The conductivity of the energizing liquid, the pressure-increasing process, the pretreatment, the heat treatment and the conductive polymer coating are strictly operated according to the parameters in the embodiment.
[0105] Electrical performance test
[0106] After the experiment was completed, the electrical performance parameters of the capacitors produced by the original process and the new process were tested respectively, and the data are as follows:
[0107]
[0108] The capacitance of the capacitors produced by the new process is similar to that of the original process, both between 84 and 98 μF. The new process (Examples 1-3) slightly reduces the range of capacitance, but the reduction is small (up to 4 μF). This shows that the new process has little effect on capacitance and basically maintains the expected capacity range.
[0109] The new process (Examples 1-3) significantly reduced the ESR value, ranging from 20 to 31 mΩ, which is about 50% better than the 45 to 65 mΩ of the original process. ESR is one of the key parameters affecting capacitor performance. Lower ESR means that the capacitor can conduct current more efficiently and reduce heat loss when working at high frequencies. Therefore, the new process performs well in improving capacitor performance.
[0110] The new process significantly reduces the leakage current (I0), which ranges from 5.8 to 180 μA, significantly lower than the 22 to 355 μA of the original process. The reduction in leakage current means that the new process plays a positive role in improving the energy efficiency and reliability of capacitors. The control of leakage current is very important to improve the life and performance stability of capacitors.
[0111] The new process significantly reduces the loss tangent (D) to 1.6-2.1%, much lower than the 4.3-4.8% of the original process.
[0112] The lower the loss tangent value, the smaller the energy loss of the capacitor and the higher the efficiency. Therefore, the new process not only improves the conductivity of the capacitor, but also reduces energy loss and improves overall performance.
[0113] By comparing the electrical performance parameters of chip-type polymer tantalum electrolytic capacitors produced by the original process and the new process (based on Examples 1-3), the results show that the new process is significantly superior to the traditional process in multiple key electrical properties:
[0114] The ESR value, leakage current and loss tangent are all significantly improved, indicating that the new process can effectively improve the high-frequency performance, energy efficiency and stability of the capacitor.
[0115] The change in capacitance is small, that is, the impact of the new process on capacitance is relatively mild and basically remains within an acceptable range.
[0116] The new process has higher production efficiency and lower energy loss, which improves the economy of the manufacturing process while ensuring the performance of the capacitor.
[0117] The above embodiments of the present invention are not intended to limit the protection scope of the present invention, and the implementation modes of the present invention are not limited thereto. All other modifications, replacements or changes made to the above structures of the present invention based on the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, should fall within the protection scope of the present invention.
Claims
1. A method for manufacturing a chip-type polymer tantalum electrolytic capacitor, characterized in that: Use the following steps: Tantalum powder with a specific capacity of 23000uF·V / g is used to press into a tantalum embryo, and then sintered to obtain a tantalum anode block; Adjust the conductivity of the energizing solution to 1500-1700us / cm to form a uniform and dense oxide film on the surface of the anode tantalum block; The following step-by-step boost method is used for empowerment: Initial stage: the voltage gradually increases from 0V to 80V, the constant voltage time is 120 minutes, and the temperature is maintained at 90℃; Intermediate stage: After 120 minutes of constant voltage at 80V, the voltage is increased to 100V and kept constant for 120 minutes, and the temperature is maintained at 90℃. Final stage: the voltage is increased from 100V to the target enabling voltage, the constant voltage time is 180 minutes, and the temperature is gradually reduced to 80℃; The energized tantalum anode block is heat treated.
2. The method for manufacturing a chip-type polymer tantalum electrolytic capacitor according to claim 1, characterized in that: The pretreatment process of the tantalum anode block includes: preparing a pretreatment solution, mixing a silane coupling agent, glacial acetic acid and water in a volume ratio of 1:1:10, soaking the tantalum anode block for 30 minutes, taking out the tantalum anode block, and then drying it.
3. The method for manufacturing a chip-type polymer tantalum electrolytic capacitor according to claim 1, characterized in that: After heat treatment, a conductive polymer is coated on the surface of the anode tantalum block to make the conductive polymer layer evenly distributed on the surface of the anode tantalum block. The coated anode tantalum block is first dried at 80°C for 20 minutes and then dried at 150°C for 45 minutes.
4. The method for manufacturing a chip-type polymer tantalum electrolytic capacitor according to claim 1, characterized in that: The energy-enabling liquid is an electrolyte, which is an aqueous solution containing phosphate ions and oxygen ions.
5. The method for manufacturing a chip-type polymer tantalum electrolytic capacitor according to claim 1, characterized in that: The heat treatment temperature was 450° C. and the treatment time was 60 minutes.